Monitoring Heparin Therapy Using Activated Partial Thromboplastin Time – Results of a Multicenter Trial Establishing the Therapeutic Range for SILIMAT, a Reagent with High Sensitivity to Heparin - Toulon, Pierre; Boutière, Brigitte; Horellou, Marie-Hélène; Trzeciak, Marie Christine; Samama, Meyer M. (Thrombosis and Haemostasis, 1998)
APTT is widely used for laboratory monitoring of treatment with unfractionated heparin (UFH). However, since its sensitivity to heparin varies significantly from one reagent to another, the therapeutic range had to be defined for each brand of APTT reagent. As an example, SILIMAT (bio-Mérieux) is a new APTT reagent containing rabbit brain phospholipids and micronized silica as an activator. Since its high sensitivity to heparin has been previously reported, a multicenter trial was carried out in an attempt to define the therapeutic range of APTT performed using this new reagent. For that purpose, 170 blood samples drawn for routine coagulation testing from 170 different patients treated with UFH were analyzed. A single batch of two different APTT reagents were used on KC10 coagulometers: SILIMAT and Automated APTT (Organon-Teknika) whereas the anti-Xa activity was evaluated by a chromogenic substrate-based assay. The same methodology was used in all the centers. In order to obtain a plasma anti-Xa activity within the therapeutic range i.e. between 0.30 and 0.70 IU/ml, the APTT ratios were found between 1.90 and 5.40 for SILIMAT, which corresponded to clotting times of the patients plasma between 63 and 178 s. The APTT ratios were significantly lower when evaluated using Automated APTT (between 1.70 and 4.10), with clotting times between 53 and 127 s. In addition, a good correlation was found between the Anti-Xa activity and APTT for both reagents (r >0.65). However, it is not possible to make recommendations regarding the therapeutic ranges without restrictions. Although about 70% of the patients with an anti-Xa activity between 0.30 and 0.70 IU/ml had an APTT in the above defined ranges, the degree of concordance between the two assays is not absolute. Actually more than 30% of the patients had discordant anti-Xa activity and APTT and more than a quarter of the patients included in the above defined therapeutic range for APTT had an anti-Xa activity outside the 0.30-0.70 IU/ml range, whatever the reagent used. In conclusion, to define the therapeutic ranges of APTT using the recommended method is practicable but some critical points could be raised, suggesting that a better method is awaited in order to improve the standardization.